Independent development of refraction, accommodation and convergence over two years in primary school children - Maagaard, Marianne Ledet (Scandinavian Journal of Optometry and Visual Science, 2015)
Abstract Purpose: To examine whether age-related changes in refraction covary with changes in parameters describing accommodation and convergence over time in a group of Danish school children. Methods: Two-hundred and seventy-eight unselected Danish school children (7.1-13.9 years) without manifest strabismus were studied at baseline and after two years. Each examination included measurement of distance visual acuity, unilateral cover test, non-cycloplegic autorefraction, monocular amplitude of accommodation, monocular accommodation facility, near phoria, near point of convergence, and positive and negative fusional vergence. The changes in the measured parameters were studied over time, followed by the testing for dependencies in the development of these parameters. Results: After two years there was a significant increase in distance visual acuity (p=0.04), monocular accommodation facility (p<0.001), near point exophoria (p=0.04), near point of convergence (p=0.01), and fusional range (p<0.001), a significant reduction in hyperopia (p=0.01) and monocular amplitude of accommodation (p<0.001), while the midpoint of the fusional range changed significantly towards convergence (p<0.001). The increase in near point of convergence correlated significantly with the decrease in monocular amplitude of accommodation (p<0.001) and the convergent shift in the midpoint of the fusional range was significantly correlated with a larger fusional range (p<0.001). The changes in all other parameters were independent. Conclusions: The development of refraction, accommodation, and convergence parameters in school children over two years are independent. This may be due to separate processes regulating development, and suggests that therapeutic intervention may be performed on each of the parameters individually without a derived effect on the other parameters.